2019
DOI: 10.1155/2019/2978265
|View full text |Cite
|
Sign up to set email alerts
|

Wearing Time of Ankle-Foot Orthoses with Modular Shank Supply in Cerebral Palsy: A Descriptive Analysis in a Clinically Prospective Approach

Abstract: Objective. To date there is only limited knowledge about the wearing time of orthoses. Ankle-foot orthoses (AFOs) have not been studied with this research question. Additional influences of the orthotic design as well as weekdays and the weekend are also unknown. Design. Monocentric, clinically prospective intervention study. Patients. Inclusion of 10 patients with bilateral spastic cerebral palsy. Methods. Equipment of all subjects with a dynamic ankle-foot orthosis (DAFO) and modular shank supply (MSS, dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…A study of AFO-wearing time in children with CP has shown that wearing time is varying depending on the prescriber and environmental factors. 15 Therefore, the purpose of this study was to compare the body functions and structures, activity and participation levels, and environmental factors according to the AFO-wearing time in children with spastic CP at Gross Motor Function Classification System (GMFCS) levels I-III.…”
Section: Introductionmentioning
confidence: 99%
“…A study of AFO-wearing time in children with CP has shown that wearing time is varying depending on the prescriber and environmental factors. 15 Therefore, the purpose of this study was to compare the body functions and structures, activity and participation levels, and environmental factors according to the AFO-wearing time in children with spastic CP at Gross Motor Function Classification System (GMFCS) levels I-III.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence was notably varied across the studies with papers reporting considerable heterogeneity within the data. One of the papers that objectively measured usage using temperature sensors reported lower usage levels than had been recommended, 15 although with so few papers in this review, this is not a firm finding and would benefit from being investigated in greater detail in the future. One paper in the review compared methods to measure AFO usage and identified variation in recorded wear times according to the monitoring method used.…”
Section: Usagementioning
confidence: 77%
“…16 One paper reported lower wearing times than had been recommended by clinicians. 15 Variation in usage times was seen across the participants in both studies, 15,16 with some indication toward patterns of use. 15 A third paper in this review did discuss usage; however, Maas et al 17 describes patient adherence to a knee-ankle-foot orthoses (KAFO) style device.…”
Section: Afo Usagementioning
confidence: 90%
“…This indicates that mothers seemed to not perceive the need for their children to use the orthosis at home and also that their attitude might be influenced by insufficient information. This fact also seems to signal a failure in communication between therapists and mothers, as there is a lack of knowledge about the need for continuously using the AFO for at least 6 h when the goal is to prevent muscle shortening (Schwarze et al, 2019). Additionally, there is a lack of knowledge about the value of the AFO as a facilitating resource due to its ability to expand the activities and participation of its user, regardless of the environment frequented (McMonagle, Rasmussen, Elliott, & Dixon, 2016).…”
Section: Discussionmentioning
confidence: 99%